Adequate vitamin D level associated with reduced risk of sporadic colorectal cancer - Ma, Yanhui; Deng, Lin; Huangfu, Yuchan; Zhou, Yunlan; Wang, Ping; Shen, Lisong (Frontiers in Nutrition, 2023)
Purpose The effect of vitamin D level pertinent to colorectal cancer incidence, progression, or mortality risk is complicated, and study findings are mixed. Therefore, we evaluated whether serum vitamin D [25-hydroxyvitamin D, 25(OH)D] is associated with the incidence of sporadic colorectal cancer (CRC). Methods This study is a retrospective analysis of the relationship between serum 25(OH)D level and the risk of CRC. Age, sex, body mass index, history of polyp, disease conditions (i.e., diabetes), medications, and other eight vitamins were used as confounding factors. A total of 389 participants were enrolled in this study, including comprising 83 CRC patients without a family history and 306 healthy controls, between January 2020 and March 2021 at the Department of Colorectal Surgery and Endoscope Center at the Xinhua Hospital, Shanghai Jiao Tong University School of Medicine. Adjusted smoothing spline plots, subgroup analysis, and multivariate logistic regression analysis were conducted to estimate the relative risk between serum 25(OH)D and sporadic CRC risk. Results After fully adjusting the confounding factors, it was found that circulating 25(OH)D played a protective role in patients with CRC (OR = 0.76 [0.63, 0.92], p = 0.004) and that an adequate vitamin D level was significantly associated with a reduced CRC risk compared to vitamin D deficiency or sufficiency (OR = 0.31 [0.11, 0.9], p = 0.03). According to this study, statins did not affect the potential protective effects of vitamin D (OR = 1.02 [0.97, 1.08], p = 0.44) and may account for the inverse association between serum 25(OH)D and colorectal cancer. Conclusion An adequate level of serum 25(OH)D was associated with a reduced CRC risk, especially for the elderly. The finding on the absence of protective effect of vitamin D in the statin use subgroup, suggests it may be one of the substantial contributing confounders, and warrants further investigation.